Evaluation of Antibiotic Use in Children's Respiratory Tract Infections at Primary Health Center in Tabanan Bali - Putri, Kadek Sephia Adiana; Widowati, I Gusti Ayu Rai; Sutema, Ida Ayu Manik Partha; Reganata, Gde Palguna; Saputra, I Wayan Agus Gede Manik (Universitas Ahmad Dahlan, 2025)
Background: Respiratory Tract Infections are among the most common health problems affecting children globally, with a particularly high prevalence in Southeast Asia, including Indonesia. Inappropriate antibiotic use in treating respiratory tract infections can lead to antibiotic resistance. This study evaluates the rationality of antibiotic use in pediatric respiratory tract infections cases and assesses prescribing patterns based on established guidelines. Method: A descriptive observational study with a cross-sectional approach was conducted using purposive sampling. Data collected from 130 medical records of pediatric patients with respiratory tract infections (from January to March 2024) at a primary health care center in Tabanan, Bali were analyzed. The Gyssens method evaluated antibiotic rationality based on dosage, duration, and clinical indications. Data were analyzed descriptively to determine antibiotic prescribing patterns and compared with national antibiotic use guidelines. Results: The results showed that 46.1% of antibiotic use was included in the rational category (Category 0), while 43.1% were included in the use without clear indications (Category V). Amoxicillin is the most widely prescribed antibiotic (90.8%). These findings indicate a tendency to use antibiotics not by clinical guidelines. Conclusion: The use of antibiotics in pediatric patients with respiratory tract infections is mostly suboptimal. Interventions are needed to improve compliance with rational antibiotic use guidelines, including education for healthcare workers and ongoing monitoring of antibiotic prescribing patterns